Preparation and biomedical application of light-responsive hydrogels based on natural products - Fan, Xinyi; Shang, Haihua; Ji, Leyuan; Ma, Shitang; Liao, Maoliang (Frontiers in Pharmacology, 2025)
This article systematically reviews the light-responsive hydrogels based on natural products, with a focus on their extensive applications in the field of biomedicine. Regarding the preparation methods, the article elaborates on the physical self-assembly, chemical crosslinking agent method, photocrosslinking method, and free radical polymerization method. The biomedical application section introduces their applications in drug release and wound healing based on the mechanisms of photochemical reactions, photoisomerization reactions, and photothermal reactions. In terms of quality evaluation frameworks, the natural light-responsive hydrogels evaluation frameworks is summarized, and the shortcomings of the existing evaluation frameworks are analyzed. Finally, the article summarizes its application potential and development bottlenecks, looks forward to future research directions, and proposes targeted development suggestions, thereby promoting its wider applications in deep disease treatment and personalized medicine.